KELULUSHIDUPAN KEPITING BAKAU (Scylla spp.) DENGAN TEKNIK BUDIDAYA CRAB BALL FLOATING RAFT DI MANGROVE BAROS, BANTUL, YOGYAKARTA - Bagus Budi Priyono; Triatmanto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to determine the survival rate of Mud Crab (Scylla spp.) with the Crab ball floating raft Cultivation Technique at Mangrove Baros, Bantul, Yogyakarta. Increasing market needs and the depleting supply of mud crabs is the background or the need for this research to maintain the market demand for mud crabs. This research is experimental research. Crab ball is used as a place for cultivation by comparing the use of floating rafts. The research was conducted from 19 August 2022 to 5 November 2022 in the Baros Mangrove Area, on the Tempur River to be precise. Data collection was carried out for 2.5 months by observing the survival of the crabs every day. The environmental variables measured include temperature, dissolved oxygen, pH, and salinity. Data was collected every 2 weeks and then analyzed regarding the survival rate of mud crabs using the Survival Rate formula. The results showed that the survival of mud crabs with control treatment or without floating raft showed a rate of 44%. While the use of floating raft shows a total figure of 76%. This research was carried out on the survival of each species and the Kruskal Wallis test was carried out to determine the different treatments and to obtain sig. 0.116 which means there is no difference in each treatment. This research was conducted at a temperature range of 28.5 ℃ - 29.0 ℃, dissolved oxygen in the range of 6.2 – 7 mg/L, pH in the range of 6.8 – 7.4, and salinity in the range of 17.5 – 25.